Socio-economic Aspects of Tourism Development in Chitlang Village, Makwanpur - Lamichhane, Anjana; K. C., Anup; Sharma, Bishal (Economic Journal of Nepal, 2020)
This paper examines how the local community of Chitlang village perceives the tourism impact on their community and how their socio-economic characteristics influence their perception towards tourism. Self-administered questionnaires were interviewed to the local people. For this, a 5-point Likert-type response scale was used. Data from 54 completed questionnaires were analyzed quantitatively by various statistical techniques, including factor analysis and cluster analysis. The impacts on the local community were condensed into eight factors: community development, economic impacts, local production, local environment, youths’ consumption pattern, social impacts, occupational pattern, and land prices. Simultaneously, all respondents were segmented into six groups according to the socio-demographic factors (gender, age, education level, and occupation) by cluster analysis. The relationship between eight factors concerning tourism’s impacts and those six clusters groups with different socio-demographics were established. Educated youth were paying great attention to economic benefits and were concerned with the positive and negative impact of tourism on the local environment. Senior citizens with lower education levels perceived development of the locality from tourism, and other adult groups saw changes in occupational pattern changes.